Old subjects with sepsis in the emergency department: trend analysis of case fatality rate - Fabbri, Andrea; Marchesini, Giulio; Benazzi, Barbara; Morelli, Alice; Montesi, Danilo; Bini, Cesare; Rizzo, Stefano Giovanni (BMC geriatrics, 2019)
The burden of sepsis represents a global health care problem. We aimed to assess the case fatality rate (CFR) and its predictors in subjects with sepsis admitted to a general Italian hospital from 2009 to 2016, stratified by risk score. We performed a retrospective analysis of all sepsis-related hospitalizations after Emergency Department (ED) visit in a public Italian hospital in an 8-year period. A risk score to predict CFR was computed by logistic regression analysis of selected variables in a training set (2009-2012), and then confirmed in the whole study population. A trend analysis of CFR during the study period was performed dividing patient as high-risk (upper tertile of risk score) or low-risk. Two thousand four hundred ninety-two subjects were included. Over time the incidental admission rate (no. of sepsis-related admissions per 100 total admissions) increased from 4.1% (2009-2010) to 5.4% (2015-2016); P < 0.001, accompanied by a reduced CFR (from 38.0 to 18.4%; P < 0.001). A group of 10 variables (admission to intensive care unit, cardio-vascular dysfunction, HIV infection, diabetes, age ≥ 80 years, respiratory diseases, number of organ dysfunction, digestive diseases, dementia and cancer) were selected by the logistic model to predict CFR with good accuracy: AUC 0.873 [0.009]. Along the years CFR decreased from 31.8% (2009-2010) to 25.0% (2015-2016); P = 0.007. The relative proportion of subjects ≥80 years (overall, 52.9% of cases) and classified as high-risk did not change along the years. CFR decreased only in low-risk subjects (from 13.3 to 5.2%; P < 0.001), and particularly in those aged ≥80 (from 18.2 to 6.6%; P = 0.003), but not in high-risk individuals (from 69.9 to 64.2%; P = 0.713). Between 2009 and 2016 the incidence of sepsis-related hospitalization increased in a general Italian hospital, with a downward trend in CFR, only limited to low-risk patients and particularly to subjects ≥80 years.